Glucosylceramide synthase promotes Bcl-2 expression via the ERK signaling pathway in the K562/A02 leukemia drug-resistant cell line - Wang, Qian; Zou, Jian; Zhang, Xiufen; Mu, Huijun; Yin, Ying; Xie, Ping (International journal of hematology, 2014)
Multidrug resistance (MDR) to chemotherapeutic agents is a major obstacle to curative treatment of cancer. In various types of cancers, overexpression of glucosylceramide synthase (GCS) has been observed to be associated with MDR, thus making GCS a target for reversal of resistance. Our previous work demonstrated that GCS and Bcl-2 are co-overexpressed in the K562/A02 leukemia multidrug-resistant cell line compared with its sensitive counterpart, K562. In the present study, we investigated the effects of GCS on apoptosis in K562/A02 and the associated molecular mechanisms. Our results indicate that the inhibition of GCS caused downregulation of Bcl-2 as well as apoptosis enhancement in response to ADM via the ERK pathway, while JNK or p38 MAPK signaling appeared to play less significant roles in the regulation of apoptosis and MDR in K562/A02 cells. Targeting GCS by siRNA also enhanced ceramide accumulation, which is involved in GCS knockdown-induced inhibition of ERK activation and Bcl-2 expression levels.